Viability of Commodity Exchange in Bhutan: Assessing Challenges and Benefits - Amir Gurung; Phuntsho Choden; S. Daly; K.B Singh (AIBPM Publisher, 2021)
This paper investigates the viability of commodity exchange in Bhutan and identifies its essential pre-conditions. Challenges and benefits are enumerated using exploratory and qualitative research with open-ended and semi-structured interviews. Bhutan represents an emerging South-Central Asian country successful emergence of which into the global arena in the last fifty years could serve as an example for other small and developing markets. The results of this study put challenges for farmers in two categories, before and after harvest. All post-harvest challenges can be addressed through an established commodity exchange and its three pre-conditions are essential to the development of commodity exchange in Bhutan.